Introduction to Bayesian Statistics, Third Edition. By William M.Bolstad and James M.CurranHoboken, New Jersey: John Wiley and Sons. 2017. 601+xvi pages. AUD 219.95 (hardback). ISBN 9781118091562. (6th June 2019) - Parry, Matthew
Abstract : We review techniques from computer science, exploiting the graph structure for exact and approximate inference in graphical models.